Quem irá cuidar de nós? desproteção dos idosos na região do Butantã - São Paulo - Medeiros, Ana Paula Roland Rocha (2015)
The present study resulted from 20 years of practice as a social worker with experience in the healh field and primarily engaged in service provision for the elderly. The growth of the elderly population and longevity are worldwide phenomenom that encompass all social-economic classes. If, in one hand, longevity means social conquest, on the other hand, it might mean people growing old the "hard way", without enough financial benefits to cover their basic needs. The goal of the present study was to gather information on the needs and demands of the elderly living in the Butantã region as recorded in reports written by CRAS Butantã professionals. Both qualitative and quantitative methodologies were used. After a careful review of the pertinent literature, research participants were selected based on reports from social workers on Home visits performed between march and december 2014, after contact through the Disque 100 hotline. Data gathering and analises employed estudo documental bibliográfico and non-participant observation methodologies. Results reinforce the hypothesis that the elderly of Butantã don't have their needs met and are unprotected. They are victims of what is known in the literature as structural violence, which has aspects of social inequality, poverty and discrimination expressed in many different ways. We have made immense progress in the legislation that protect the elderly population, but that progress seem to still be only words on pape